SOCIO-EPIDEMIOLOGICAL EVALUATION OF TUBERCULOSIS AND IMPACT OF PHARMACEUTICAL CARE ON MEDICATION ADHERENCE AMONG TUBERCULOSIS PATIENTS - THOMAS, ARATHY; Joy, Joyal; Kurian, Alan; V, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: Tobjective of this study is to assess the knowledge and to monitor medication adherence among tuberculosis (TB) patients. Methods: During the 6 months prospective interventional study, a data collection form was designed. The knowledge and adherence levels were assessed using quantified questionnaires. Patients were counseled using patient information leaflets and reassessed during follow-up. Results: Results were analyzed using one-way ANOVA and Pearson's correlation. Key findings: Among the 65 patients who completed 3 reviews during 6-month follow-up study, there was a statistically significant improvement in medication adherence score from baseline in correspondence with the increase in knowledge baseline to first follow-up revealed a mean increase in medication adherence level of 2.723Â±1.625 (p<0.05) in correspondence with a mean increase in knowledge level 24.8Â±5.04 (p<0.05) which is statistically significant. First follow-up to second follow-up showed a mean increase in medication adherence of 1.400Â±1.072 (p<0.05) in correspondence with a mean increase in knowledge level 28.32Â±4.4 (p<0.05) which is statistically significant. Second to third follow-up showed a mean increase in medication adherence of 0.123Â±0.450 (p<0.05) in correspondence with a mean increase in knowledge level 34.18Â±2.74 (p<0.05) which is statistically significant. Conclusion: The efforts to improve awareness on TB patients such as providing patient counseling and education could enhance adherence to therapies and thus could improve outcomes and quality of life.